The Effect of Tai Chi Exercise on Reducing Blood Sugar Levels in Type II Diabetes Mellitus Patients at Andalas Public Health Center - Melisa Andora; Revi Neini Ikbal; Hidayatul Rahmi (STIKes Alifah Padang, 2023)
The incidence of DM in Indonesia according to the Indonesian Ministry of Health in 2021 is 19.47 million. The Ministry of Health predicts an increase in the number of people with DM in Indonesia by 19.9% in 2030 to around 21.3 million. This can also be seen from the increasing incidence of DM at the Andalas Health Center in the city of Padang, in 2021 there were 819 people and in 2022 there were 823 people. One of the risk factors for an increase in blood sugar levels is a lack of physical activity and regular exercise, which causes an increase in blood sugar levels in people with diabetes mellitus. The purpose of this study was to determine the effect of tai chi gymnastics on reducing blood sugar levels in patients with type II diabetes mellitus at the Andalas Public Health Center in Padang City in 2023. The research design is called quantitative with a quasi-experimental design with pre and post-tests with cross-sectional. The population of people with diabetes mellitus from October-December 2022 is 370 people with a sample of 23 people. The research was conducted from March to August 2023. Data was collected using observation sheets and then analyzed univariately and bivariately using the Paired T-Test. The results showed that the average blood sugar level of patients before exercise was 259.61. The average blood sugar level after exercise is 244.48. Based on the statistical test, the p-value = 0.000 was obtained. Based on the research conducted, it can be concluded that there is an effect of tai chi gymnastics on reducing blood sugar levels in patients with type II diabetes mellitus.